Innovation and Strategic Planning in Education: Realizing Sustainable and Competitive Education - Aini, Nurul (Transformation of Islamic Management and Education, 2024)
This research explores the development of sustainable and competitive education through comprehensive planning strategies in educational institutions. It aims to evaluate the effectiveness of strategic approaches in curriculum design, human resource management, and technology use in preparing students for global challenges. The study adopts a survey method with a quantitative approach, collecting data from a diverse range of respondents to assess their perceptions of sustainable education. Data was gathered through questionnaires and analyzed using descriptive statistical techniques to examine perceptions related to educational sustainability, soft skills development, technology readiness, and curriculum evaluation. The findings reveal that 85% of respondents acknowledge the importance of education in not only addressing immediate needs but also preparing students with relevant skills for the future. Regular teacher training on technology-based teaching methods, such as e-learning platforms, was identified as a crucial step, along with the need for schools to collaborate with local industries to align curricula with industry demands and offer internships to develop practical skills. Furthermore, 78% of respondents considered technology an essential factor in education, although infrastructure limitations remain a challenge in some regions. This study suggests that education in Indonesia must strengthen strategic planning, particularly in integrating soft skills and improving technological infrastructure, to create more inclusive and adaptive educational systems. Recommendations include fostering collaborations with external sectors to enhance the development of sustainable, globally competitive education.